Recurrence relations for the three-dimensional Ising-like model in the external field - Kozlovskii, M.P. (Condensed Matter Physics, 2005)
The method for calculation of the partition function of lattice model for the magnet in the external field near critical point (CP) is proposed. The recurrence relations and their explicit solution near the critical point are founded. It is shown that dependence on temperature of thermodynamic functions near CP, when the field value comes down to zero, is in good agreement with the previous results obtained using the collective variable method. The phase transition temperature (when h = 0) is calculated and the dependence on parameters of interaction potential is found. Запропонований метод розрахунку статистичної суми граткової моделі магнетика в зовнішньому полі поблизу критичної точки. Знайдені рекурентні співвідношення та їхній явний розв’язок поблизу фіксованої точки. Показано, що в границі, коли величину поля спрямувати до нуля, приходимо до результатів, отриманих раніше в методі колективних змінних у випадку відсутності зовнішнього поля. Розрахована температура фазового переходу (при h = 0) та знайдена її залежність від параметрів потенціалу взаємодії.